Prognostic impact of eosinophils in peripheral blood and tumor site in patients with esophageal squamous cell carcinoma treated with concurrent chemoradiotherapy. Issue 3 (22nd January 2021) - Yang, Xiyue; Wang, Lei; Du, Huan; Lin, Binwei; Yi, Jie; Wen, Xuemei; Geng, Lidan; Du, Xiaobo
Abstract : Abstract: To date, no effective biological markers have been identified for predicting the prognosis of esophageal cancer patients. Recent studies have shown that eosinophils are independent prognostic factors in some cancers. This study aimed to identify the prognostic impact of eosinophils in esophageal squamous cell carcinoma patients treated with concurrent chemoradiotherapy (CCRT). This study enrolled 136 patients who received CCRT for locally advanced unresectable esophageal squamous cell carcinoma (ESCC). We evaluated the survival time and clinical pathological characteristics of eosinophils. The Kaplan–Meier method was used to estimate survival data. The log-rank test was used for univariate analysis and the Cox proportional hazards regression model was used to conduct a multivariate analysis. Kaplan–Meier analysis revealed that high eosinophil infiltration correlated with better overall survival (OS) ( P  = .008) and better progression-free survival (PFS) ( P  = .015). The increase in absolute eosinophil count after CCRT also enhanced OS ( P  = .005) and PFS ( P  = .007). The PFS and OS in patients with high blood eosinophil count before CCRT (>2%) was better than those with low blood eosinophil count(<2%) ( P  = .006 and P  = .001, respectively). Additionally, the multivariate analysis revealed that disease stage and high eosinophil infiltration, increased peripheral blood absolute eosinophil count after CCRT, and high peripheral blood eosinophil count before CCRT were independent prognostic indicators. High eosinophil count of tumor site, increased peripheral blood absolute eosinophil count after CCRT, and high peripheral blood eosinophil count before CCRT are favorable prognostic factors for patients with ESCC treated with CCRT.